Screening beyond conventional serological markers for hepatitis B and C viruses in cirrhosis: an entity overlooked - ., Manjri; Katyal, Virender; Yadav, Deepak; Goyal, Sandeep (International Journal of Research in Medical Sciences, 2020)
We aimed to emphasise the role of screening beyond conventional serological markers (HBsAg and Anti HCV antibodies for chronic viral hepatitis B and C respectively) in patients with cirrhosis. Patients with cirrhosis of liver are often labelled as having cryptogenic cirrhosis (CC), if no etiology is found. In chronic viral hepatitis B and C (CHB and CHC) induced cirrhosis, HBsAg and Anti HCV antibodies respectively are usually done to rule out the viral infections however their absence have been documented in subset of patients having these infections. In this regard, we hereby present a case labelled as CC and developed HCC; later on, further evaluation turned out to be having both CHB and CHC. A 51-year-old male with diabetes presented with index episode of hemetemesis. On further evaluation he was diagnosed to have cirrhosis of liver. No etiology was found and he was labeled as cirrhosis secondary to Non-alcoholic steatohepatitis (NASH)/cryptogenic cirrhosis. Later on, he developed hepatocellular carcinoma (HCC). We evaluated the patient with HBV DNA and HCV RNA levels keeping possibility of occult hepatitis B (OBI)/ seronegative hepatitis C infection despite HBsAg and Anti HCV antibodies being negative. Both levels were found to be raised and we attributed cirrhosis to dual hit by CHB and CHC. Patient was managed with antiviral drugs successfully with no recurrence of HCC and control of blood sugar levels. We hereby stress that screening beyond the HBsAg and Anti HCV antibodies should be done in all cases of liver cirrhosis in which etiology is not found on initial screening.